A REVIEW ON THERAPEUTIC VALUE OF FENUGREEK (International Association of Biologicals and Computational Digest, 2023)
Fenugreek, a herb with a long history in medicine and nutritional value, is one of the most promising ones. Green leaves and seeds from this plant have several uses. Due to their high fiber content and capacity to alter the texture of food, 100 gm of seeds supply more than 65% of the daily need for dietary fiber (Murlidhar et al., 2012). This plant has a wide range of applications in traditional medicine due to its medicinal alkaloids, steroid compounds, and sapogenins. This plant has been used as a general tonic to boost metabolism as well as to ease childbirth and promote digestion. Trigonelline, which is highly helpful in treating diabetes and lowering blood cholesterol, is thought to be the most significant metabolite of fenugreek (Bahmani et al., 2016).
Keywords: fenugreek, medicinal plants, Therapeutic values